A Major Scottish Tramp Ship and Liner Company: Andrew Weir’s Bank Line – 1875-2016. Part 2, 1970-2016 - Fenton, Roy; Murphy, Hugh (The Northern Mariner / Le marin du nord, 2025)
Following on from Part 1, (The Northern Mariner/Le marin du nord 34, no. 3 (2024)), Part 2 considers the later history of Andrew Weir’s Bank Line and its subsidiary shipping companies from 1970 through changes in name of its shipping operation to dissolved company status in 2016. As in Part 1, in tandem we also trace the history of Bank Line’s holding company, Andrew Weir and Co. Ltd.